Mapping of Regencies/City in Bali Province Based on Education Indicators - I.K.G. Sukarsa; G.K. Gandhiadi (Jurnal Matematika, 2018)
Education Development is one of the important elements of Human Resource Development (HR). In order for education development to be carried out properly, one of the important things is to know how to map the development of education in an area (for example the regencies in this study) based on predetermined education indicators. Based on the map, it can be seen that the education indicator is dominant in an area. With this information, the direction of education development in each region can be designed according to regional conditions by increasing indicators that are relatively lacking and maintaining a good indicator. This study aims to produce information in the form of education development maps in regencies/city in Bali Province based on education indicators so that they can be used as a reference for education development policies in each regencies. The resulting map will provide information on the condition of education indicators in a regencies. To get an overview of the map, Biplot Analysis is carried out on education indicator data. This analysis will provide a graph of the position of objects (regencies / city) and the relationships between variables (education indicators) simultaneously. The results of the analysis in graphical form with biplot shows that Gianyar Regency and Tabanan Regency are regencies that generally have close characteristics. This means that based on education indicators, the two regencies have similar indicators. The same thing is also seen in Karangasem and Bangli . While 5 (five) other regencies / city appear to have different indicator characteristics, the position of each regencies or city is far apart.